Effect of Drinking Water on Image Quality FDG PET/CT Scan Test and How Can Water Reduce the Radiation In Human Body - Mawat, Mazin (Indonesian Journal Publisher, 2025)
The study focuses on the role of water in reducing radiation exposure during FDG PET/CT scans. Water consumption prior to the scan hydrates the body, improves blood circulation, and facilitates efficient distribution uptake of the radioactive tracer, FDG. This leads to more accurate detection of areas with high metabolic activity, such as cancer cells. Furthermore, water reduces the concentration of residual FDG in the bladder or kidneys, having a low radioactive count during the image capture. After the scan, isotonic is achieved with aid of water to eliminate any remaining FDG as a move towards minimizing radiation consequences. The research also focuses on the type of radiation, dividing it into ionizing radiation and non-ionizing radiation as well as the hazards of radioactive substances. The paper explores the nature of tumors, the working of PET and CT equipments, and synergistic impact of PET/CT. Pet: The focus is on one more radioactive material – FDG which is used widely in pet scan and its properties like half-life, shelf-life, composition and where it gets energy from.